Answer:
Im not fully sure but I think it is negative 2 and negative 3
Answer:
The expression that could be used is (-4)(3) + (-4)(
) ⇒ B
Step-by-step explanation:
Let us revise the distributive property:
<em>The product of a number and the sum of 2 other numbers equal to the sum of the products of the number with the other 2 numbers</em>
We will use this rule to solve the question
∵ The product of -4 and 3
= -4 × 3
→ We can right 3
as (3 +
)
∵ 3
= (3 +
)
∴ -4 × 3
= -4(3 +
)
→ By using the rule above
∵ -4(3 +
) = (-4)(3) + (-4)(
)
∴ -4 × 3
= (-4)(3) + (-4)(
)
∴ The expression that could be used is (-4)(3) + (-4)(
)
It's asking you to shift the graph of; y = 5x up 3 units. if you add 3 to the equation, all y-values will be increased by 3 this shifts the graph up exactly 3 units.
y = 5x + 3
x - y = - 11 .............( 1 )
y + 7 = - 2x ...............( 2 )
from equation ( 1 )
x - y = - 11
x = -11 + y ...........( 3)
putting x in equation ( 2 )
y + 7 = - 2 x
y + 7 = -2 ( -11 + y ) y + 7 = 22 - 2 y y + 2 y =22 - 7
3 y = 15 y = 15 / 3
putting value of y in equation 3
x = -11+ ( 13 /5 ) x = -33 /3 + 15 / 3 ( l.c.m)
x = -17 / 5
check
x = -11 + y
- 17 / 5 = -11 + 13 / 5
-17 /5 = -17 / 5